Pharmaceutical attention in the treatment of obesity involving analogues of Glucagon-like peptide 1 (GPL-1) (Research, Society and Development, 2022)
The general objective of this article is to explore the knowledge about injectable pharmacological therapy in obesity, while it intends to raise the available evidence regarding the benefits, side effects, and the probable off-label use, involving the Glucagon-like peptide analogues. 1 (GLP-1) used in this treatment. This is an exploratory, integrative literature review study on the impact of pharmaceutical care on injecting drug use in the treatment of obesity. The search for studies was carried out in the electronic databases: NCBI/PubMed, Google Scholar, SciELO and Lilacs - Bireme. The inclusion criteria were: articles available in full, in Portuguese and English, from 2015 to 2022 with free access and that had an affinity with the theme. A total of 40 publications were identified, after applying the inclusion criteria, 24 studies remained. In the selected articles, we identified that GLP-1 receptor agonist drugs have been developed, with mimetic action to the endogenous peptide, prescribed for the treatment of obesity. Liraglutide (Saxenda® and Victoza®) and Semaglutide (Ozempic®), both synthetic GLP-1 incretin analogues, proportionally increase glucose-dependent insulin secretion, reduce glucagon secretion, delay gastric emptying, and decrease appetite, with agonist action on its receptors, resulting in weight loss. In this context, the pharmacist's performance aimed at patients suffering from obesity disorder includes, in addition to evaluating the treatment and guiding the patient, to promote and introduce healthy lifestyle habits.